Succession og samfundsøkonomisk effektivitet - Niels Blomgren-Hansen (Copenhagen Business School (CBS), Department of Economics, 1999)
– As a main principle, income is taxed when earned. This principle is broken in case of unrealized capital gains (recovered depreciations, unrecorded intangible assets etc.). Such incomes are taxed when realized or the `latent tax' is passed on to the new owner (tax succession). In Denmark, tax succession is allowed only if the new owner is a close relative to the previous owner. However, recently it has been proposed to extend the access to tax succession to a wider group of potential purchasers as a means of facilitating generational chances in small and medium sized firms. One argument is that taxation of capital gains gives the previous owner an incentive to delay the generational change longer than appropriate from an efficiency point of view (the `lock-in' effect). Sections 2 and 3 analyse, within a very simple framework, the impact of tax succession on the price of a firm, the after-tax revenue to the previous owner, and the tax proceeds. The conclusion is that tax succession has significant effects on before-tax and after-tax prices and that the associated indirect tax subsidy is an appreciable expenditure. Sections 4 and 5 address the problem of efficiency losses from tax succession and `lock-in. The conclusion is that, most probably, the former efficiency loss out-weighs the latter one, in particular, if the rules are discriminatory giving the previous owner an incentive to choose a less efficient purchaser who are allowed to succeed rather than a more efficient one who is not.
hdl:10398/7579
Keywords: H21; 330; Tax succession; Economic efficiency; Taxation